Influence of biologics on growth, development and yield of popcorn - Маслиёв, С. В. (Scientific Progress & Innovations, 2015)
The results of the field experiments of the influence of seed inoculation by biologics on growth, development and yield of popcorn hybrids have been given. The possibility of yield increase and product quality by seed treatment with microbial preparations as Diazofit, CL-9, Fosfoenteryn + Diazofit has been identified. The data on consumption of minerals and water have been presented. The rules of the use of biologics have been recommended. The yield of popcorn grain has been shown. The dynamics of deviation depending on the used preparation has been analyzed.